Los medios de comunicación influyen en la identidad cultural de los habitantes del sector Bellavista, cantón El Empalme, provincia del Guayas - Anchundia Troya, Eloisa Yaritza (2018)
The project is based on an analysis of the media and the influence on the cultural development of citizens, through which they learn more about our country and its roots, as well as how diversity and productiveness arise, taking into account that values and social inclusion are important at any time. The unfortunate thing is that many media project a great amount of violence that students consume in their first years and imitate the characters that appear on the screen, that is, they absorb everything that is reproduced and therefore they are exposed to bad disciplinary behavior. The problem lies in how media influence on the cultural identity of the inhabitants of the neighborhood Bellavista, El Empalme city, Guayas Province, the general objective is to determine the influence that the media have on the cultural identity of the inhabitants of the Bellavista neighborhood. To this end, several research tools have been used, such as: inductive and deductive methods, and types of research, such as descriptive and field studies, were carried out on the residents of the Bellavista neighborhood in El Empalme, province of Guayas. For this, the production of a cultural program is proposed in which music, parades, poetry, etc., are transmitted, which in any way identify the cultural customs of the area.